Smartcare : an IOT based senior care system with emergency alert / Amir Hadi Suhaimi - Suhaimi, Amir Hadi (2024)
There has been an increase in the percentage of aging population in Malaysia, which has implications in all sectors from workforce, housing, and care needs. This report aims to design a senior care system using ESP32 Microcontroller which helps facilitate the monitoring process of senior citizens. In this study, I designed a smart home system which includes low-cost sensor parts which are ultrasonic sensors. This system can be used to detect and monitor if any abnormal activity happens such as spend too long in the bathroom or sleep in a long period of time. Without the need of additional sensors only by using Millis function, this system can provide information such as the room resident is , or if he/she is actively doing his/her daily routine.t As a result, I show a working system and the ultrasonic sensors are able to detect the position of the resident, and we are even able to send an alert signal to the caretaker if any abnormal activity detected. In my opinion I believe my study can contribute to serving the elderly community which provide a monitoring system for the caretaker that is low cost. Therefore, this project helps to ease the load on nursing homes and welfare employees.by creating an IoT based senior care system